1998
DOI: 10.1037/0022-3514.75.3.617
|View full text |Cite
|
Sign up to set email alerts
|

Immune neglect: A source of durability bias in affective forecasting.

Abstract: People are generally unaware of the operation of the system of cognitive mechanisms that ameliorate their experience of negative affect (the psychological immune system), and thus they tend to overestimate the duration of their affective reactions to negative events. This tendency was demonstrated in 6 studies in which participants overestimated the duration of their affective reactions to the dissolution of a romantic relationship, the failure to achieve tenure, an electoral defeat, negative personality feedb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
989
5
19

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,181 publications
(1,089 citation statements)
references
References 58 publications
50
989
5
19
Order By: Relevance
“…It is important to note that although these results imply that interpersonal similarity increases the weight of information that presumably is less predictive of choice (i.e., secondary aspects of a decision) relative to information that should be the most predictive of choice (i.e., primary aspects of a decision), we do not argue that interpersonal similarity leads to less accurate judgments. This is because accuracy does not always follow from considering high level, general features (e.g., Gilbert, Pinel, Wilson, Blumberg, & Wheatley, 1998).…”
Section: Information Searchmentioning
confidence: 99%
“…It is important to note that although these results imply that interpersonal similarity increases the weight of information that presumably is less predictive of choice (i.e., secondary aspects of a decision) relative to information that should be the most predictive of choice (i.e., primary aspects of a decision), we do not argue that interpersonal similarity leads to less accurate judgments. This is because accuracy does not always follow from considering high level, general features (e.g., Gilbert, Pinel, Wilson, Blumberg, & Wheatley, 1998).…”
Section: Information Searchmentioning
confidence: 99%
“…A sizable literature on affective forecasting (Gilbert et al, 1998;Kahneman et al, 1999;Liberman and Trope, 1998) has shown that people typically overestimate how long positive events will make them feel good and how long negative events will make them feel bad. A number of accounts for these and related affective forecasting errors have focused on the content that is considered when making these forecasts, but little has been said about the possibility that thoughts about feelings and actual feelings might be processed by distinct neurocognitive systems, such that the system involved in forecasting might be incapable of representing certain aspects of actual experience (Kahneman et al, 1993).…”
Section: Reflective Social Cognitionmentioning
confidence: 99%
“…Affective forecasting (Gilbert et al 1998), or the process of predicting how one will feel following future events, has been shown to have powerful effects on health decision-making (Elwyn and Miron-Shatz 2010;Halpern and Arnold 2008). Despite the influence that affective forecasts can have on major life choices, these predictions often inaccurately portray actual responses (Wilson and Gilbert 2003).…”
Section: Introductionmentioning
confidence: 99%